A Community-University Approach to Substance Abuse Prevention - Lola Baydala; Fay Fletcher; Melissa Tremblay; Natasha Rabbit; Jennilee Louis; Kisikaw Ksay-yin; Caitlin Sinclair (The University of Alabama, 2022)
In response to high rates of substance abuse in their communities, members of the Maskwacis four Nations invited university researchers to partner in culturally adapting, implementing, and evaluating an evidence-based substance abuse and violence prevention program, the Life Skills Training program (Botvin & Griffin, 2014). This project used a community-based participatory research (Israel, Schulz, Parker, & Becker, 1998; Minkler & Wallerstein, 2003) approach, and was carried out by university and First Nation community partners. To evaluate the impact of the adapted program, students completed pre and post questionnaires, and community members participated in focus groups. The adapted Maskwacis Life Skills Training program was delivered in schools for three years. Students' knowledge increased significantly during program delivery, and strong support was documented from community members. This project demonstrates the impact that can be facilitated by culturally adapting and delivering a prevention program, and by forming a community-university partnership.